Hochu-ekki-to enhanced airway ciliary beating by an [Ca2+]i increase via TRPV4 in mice - Yukiko Ikeuchi-Yamamoto; Haruka Kogiso; Daichi Saito; Kotoku Kawaguchi; Riko Ikeda; Shinji Asano; Toshio Inui; Yoshinori Marunaka; Takashi Nakahari (Elsevier, 2022)
Background: Hochu-ekki-to (TJ-41, a traditional herbal medicine) is used for preventing airway infections caused by viruss or bacterias in patients with chronic obstructive pulmonary disease (COPD). TJ-41 is known to inhibit viral adhesion and to activate mucosal immune system. However, the effects of TJ-41 on the beating cilia, which sweep away inhaled viruses and bacteria from the airways (mucociliary clearance, a host defense mechanism of lungs), still remain uncertain. Hypothesis/purpose: TJ-41 may activate the airway ciliary beating, activation of which increases the rate of mucociliary clearance leading to inhibit airway infections. Methods: TJ-41 was orally administered to mice for 4-8 weeks (1.7 - 1.8 g/kg/day) and airway ciliary cells were isolated from the lungs. The frequency (CBF) and angle (CBA, an index of amplitude) of ciliary beating were measured using the high-speed video microscopy (HSVM, 500 fps), in relation to intracellular Ca2+ concentration ([Ca2+]i). Differences were considered significant p<0.05. Results: The TJ-41 treatment enhanced the basal CBF and CBA of airway cilia by 10% mediated via an increase in [Ca2+]i. Moreover, ionomycin (IM) at 1 nM increased CBF and CBA by elevating [Ca2+]i in airway ciliary cells from TJ-41 treated mice, but never in those from non-TJ-41 treated mice. These increases in [Ca2+]i were caused by the enhancement of temperature-dependent Ca2+ entry pathways, including transient receptor potential vanilloid 4 (TRPV4). Conclusion: TJ-41 enhanced the basal CBF and CBA of airway cilia via a temperature-dependent [Ca2+]i increase and it also enhanced increases in CBF, CBA and [Ca2+]i stimulated by 1 nM IM, which never increased CBF and CBA in cells from non-treated mice. Thus, TJ-41 enhanced the temperature-dependent Ca2+ entry pathways including TRPV4. The [Ca2+]i increase, a novel action of TJ-41, may induce various pharmacological activities already reported including activation of the airway ciliary beating. These results suggest the potential of therapeutic use for patients suffering from chronic disease to improve various activities in addition to prevention of airway infections.